Government Strategy towards Community Based Tourism in The Management of Seven-Level Waterfall in Bukit Berantai Village, Batang Asai District, Sarolangun Regency - Pratama, Wiranto Yoga; Prawira, Ilham Abdi; Nuur, Muhammad (PUBLICUS : JURNAL ADMINISTRASI PUBLIK, 2025)
This study examines the implementation of Community-Based Tourism (CBT) around the Seven Level Waterfall in Bukit Berantai Village, Batang Asai District, Sarolangun Regency, and evaluates the strategic role of local and village governments in developing sustainable community-based tourism. The research addresses the critical need for effective government strategies in managing tourism destinations that empower local communities while preserving environmental and cultural heritage. Using a qualitative research approach, this study conducted in-depth interviews with local government officials, village administrators, tourism stakeholders, and community members to gather comprehensive insights into current management practices and challenges. Data collection involved systematic field observations, participatory research methods, and thorough analysis of tourism-related policy documents and regulatory frameworks. The theoretical foundation integrates tourism management principles with SWOT analysis methodology to identify internal strengths and weaknesses alongside external opportunities and threats facing the destination. Findings reveal that while the Seven Level Waterfall possesses significant natural tourism potential, current management faces substantial challenges including inadequate infrastructure, limited accessibility, insufficient promotional activities, lack of professional tourism services, and poor connectivity. The study identifies key strategic principles essential for sustainable tourism development, emphasizing community ownership, participatory decision-making, equitable benefit distribution, environmental conservation, and cultural preservation. Results demonstrate that effective government intervention as both facilitator and regulator is crucial for establishing comprehensive tourism management frameworks that enhance community empowerment, economic development, and destination sustainability, ultimately contributing to the broader goals of rural development and poverty alleviation.